Fretting-corrosion in hip taper modular junctions: The influence of topography and pH levels – An in-vitro study. (June 2021) - Royhman, Dmitry; Pourzal, Robin; Hall, Deborah; Lundberg, Hannah J.; Wimmer, Markus A.; Jacobs, Joshua; Hallab, Nadim J.; Mathew, Mathew T.
Abstract: Contemporary hip implants feature a modular design. Increased reported failure rates associated with the utilization of modular junctions have raised many clinical concerns. Typically, these modular interfaces contain circumferential machining marks (threads or microgrooves), but the effect of the machining marks on the fretting-corrosion behavior of total hip implant materials is unknown. This study reports the effects of microgrooves on the fretting-corrosion behavior of hip implant materials. The flat portions of two cylindrical, polished, CrCrMo alloy pins were loaded horizontally against one rectangular Ti alloy rod. Two surface preparation groups were used for the Ti6Al4V rod (polished and machined). The polished group was prepared using the same methods as the CoCrMo pins. The machined samples were prepared by creating parallel lines on the rod surfaces to represent microgrooves present on the stem tapers of head-neck modular junctions. Newborn calf serum (30 g/L protein content; 37 °C) at pH of levels of 7.6 and 3.0 were used to simulate the normal joint fluid and a lowered pH within a crevice, respectively. The samples were tested in a fretting corrosion apparatus under a 200N normal force and a 1Hz sinusoidal fretting motion with a displacement amplitude of 25 μm. All electrochemical measurements were performed with a potentiostat in a three-electrode configuration. The results show significant differences between machined samples and polished samples in both electrochemical and mechanical responses. In all cases, the magnitude of the drop in potential was greater in the machined group compared to the polished group. The machined group showed a lower total dissipated friction energy for the entire test compared to the polished group. Additionally, the potentiostatic test measurements revealed a higher evolved charge in the machined group compared to the polished group at both pH conditions (pH 7.6 and 3.0). The machined surfaces lowered the overall dissipated friction energy at pH 7.6 compared to pH 3.0, but also compromised electrochemical performance in the tested conditions. Therefore, the role of synergistic interaction of wear and corrosion with surface topographical changes is evident from the outcome of the study. Despite the shift towards higher electrochemical destabilization in the machined group, both polished and machined groups still exhibited a mechanically dominated degradation.